Comparing the effectiveness of a computer-based English courseware to conventional classroom instruction in teaching vocabulary sets / Rafidah Abd Karim and Norbaiti Tukiman - Abd Karim, Rafidah; Tukiman, Norbaiti (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
A suitable method for English language learning is important to determine the effectiveness of mastering this language. Thus, this study investigated the effectiveness of using English Computer-based Courseware and the students’ attitude towards the learning of basic vocabulary sets among sixty Form One students at a selected rural secondary school in Malaysia. This study is to determine whether there was a significant relationship between the students’ attitude towards the use of computer courseware and their English vocabulary skills performance. T-test results showed that the use of computer courseware approach was more effective than the use of conventional classroom instructions in enhancing students’ vocabulary skills performance and the students generally had positive attitudes toward the use of English Computer-based Courseware in learning vocabulary sets in the classroom. Finally, the study concluded that there was a statistically significant relationship between the students’ attitudes towards the use of computer-based courseware and their vocabulary skills performance.